Interleukin 18 promotes myofibroblast activation of valvular interstitial cells. (15th October 2016) - Zhou, Jingxin; Zhu, Jinfu; Jiang, Li; Zhang, Busheng; Zhu, Dan; Wu, Yanhu
Abstract: Background: Calcific aortic valve disease is the main heart valve disease in the elderly. Valvular interstitial cells (VICs) play an important role in the process of valve calcification. Interleukin 18 (IL-18) is expressed in stenosis aortic valves and is positively related with the clinical severity of aortic stenosis. However, the role of IL-18 in aortic valve calcification remains unclear. This study examined whether IL-18 promotes myofibroblast and/or osteoblast transdifferention of VICs. Porcine VICs were isolated and treated with recombinant porcine IL-18. Methods: Porcine VICs were cultured and treated with IL-18. Gene and protein expression of myofibroblastic and osteoblastic markers were tested and nuclear factor κB (NF-κB) phosphorylation was also analyzed. Alkaline phosphatase (ALP) staining and activity assay were also performed. Results: Our experiments demonstrated that IL-18 significantly enhanced alpha-smooth muscle actin (α-SMA) gene and protein expression. IL-18 treatment also promoted the expression of osteopontin (OPN) and runt-related transcription factor 2 (Runx2) mRNA, although OPN and Runx2 protein expressions were not changed. IL-18 could induce ALP activity in the presence of conditioning medium. We also demonstrated that IL-18 markedly enhanced NF-κB p65 phosphorylation in VICs. Conclusions: Together these results suggest that IL-18 promotes the myofibroblast differentiation of VICs and accelerates calcification in the presence of conditioning medium via the NF-κB pathway.